2011 IEEE International Test Conference 2011
DOI: 10.1109/test.2011.6139174
|View full text |Cite
|
Sign up to set email alerts
|

Forward prediction based on wafer sort data — A case study

Abstract: This paper studies the potential of using wafer probe tests to predict the outcome of future tests. The study is carried out using test data based on an SoC design for the automotive market. Given a set of known failing parts, there are two possible approaches to learn. First a single binary classification model can be learned to model all failing parts. We show that this approach can be effective if the failing parts are compatible in learning. Second, an individual outlier model can be learned for each faili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…A forward prediction methodology was derived in [10] that studied the potential of using parametric wafer probe test measurements to predict parts that fail at final test and on the customer's side. When predicting customer returns, the authors used PCA on a set of important tests that best describe the customer return's failing behavior and an outlier model was built to screen out returns.…”
Section: Prior Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…A forward prediction methodology was derived in [10] that studied the potential of using parametric wafer probe test measurements to predict parts that fail at final test and on the customer's side. When predicting customer returns, the authors used PCA on a set of important tests that best describe the customer return's failing behavior and an outlier model was built to screen out returns.…”
Section: Prior Related Workmentioning
confidence: 99%
“…This work employs two learning techniques previously suggested: (1) applying PCA to correlated tests proposed in [1] and (2) applying PCA in conjunction with SVM [2][3] one-class outlier analysis proposed in [10]. The goal is to develop a methodology to apply these learning techniques before and after examples of customer returns become available.…”
Section: Prior Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors identified redundant tests belonging to one insertion and suggested that more expensive tests could be replaced with models built from those in less expensive insertions. In another example, the authors in [11] analyzed parametric wafer sort data from a high quality SoC and showed the potential for building models from the test data which were capable of predicting devices likely-to-fail at final package testing. Similarly, multivariate test analysis was used in [10,12] to predict parts that would fail in the field, i.e.…”
Section: Related Workmentioning
confidence: 99%